FROM HISTORICAL TO NORMATIVE-THEOLOGICAL APPROACHES: Hadith Studies and Prophetic Tradition According to Ruggero Vimercati Sanseverino - Handayana, Sri; Budiman, Arif (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2023)
The present article is a descriptive-analytical examination of the hadith studies trend in Germany. Represented by Ruggero Vimercati Sanseverino, Professor of Hadith Studies and Prophetic Tradition at Zentrum für Islamische Theologie at the University of Tübingen Germany, it explores his methodological and didactical contribution to the hadith studies traced through his publications. This study shows that Ruggero focuses on the theological dimension of hadith, as opposed to the historical study of hadith. Ruggero investigates one of the pioneers of referential text on the science of hadith, al-Ilma’ by The Moroccan Maliki scholar al-Qadi ‘Iyad. Besides studying ‘Ulum al-Hadits literature, he also expands his research on a reference text of Sunni prophetology, al-Shifaʾbi-taʿrif Huquq al-Muṣṭafa by the same author. In line with the previous topic, he tries to answer the question of how the Prophet Muhammad should be perceived by doing a critical study of prophetology according to ʿAbd al-Ḥalim Maḥmud. Ruggero also offers a comprehensive thematic approach concerning prophetological themes to counter fundamentalism and solve the conflict in some Muslim communities. The theological approach to hadith offered by Ruggero defines hadith as transmitted testimony. While classical hadith studies which places hadith as a source for prophetic tradition focusing on transmission and Orientalism/Islamic Studies put hadith as history and document which portrayed social and culture of past Muslim societies, Ruggero wants to integrate both approaches and brings them into dialogue.[Artikel ini adalah analisis deskriptif-analitik dari tren studi hadits di Jerman. Diwakili oleh Ruggero Vimercati Sanseverino, Profesor Studi Hadits dan Tradisi Nabi di Zentrum für Islamische Theologie di Universitas Tübingen Jerman, tulisan ini mengeksplorasi kontribusi metodologis dan didaktis pada studi hadis yang ditelusuri melalui publikasinya. Kajian ini menunjukkan bahwa Ruggero berfokus pada dimensi teologis hadis, berlawanan dengan kajian sejarah hadis. Ruggero menyelidiki salah satu perintis kitab referensi pada ilmu hadits, al-Ilma 'oleh ulama Maliki Maroko al-Qadi 'Iyad. Selain mempelajari literatur Ulum al-Hadits, ia juga memperluas penelitiannya pada teks referensi kenabian Sunni, al-Shifaʾbi-taʿrif Huquq al-Muṣṭafa oleh penulis yang sama. Sejalan dengan topik sebelumnya, ia mencoba menjawab pertanyaan bagaimana seharusnya Nabi Muhammad dipandang dengan melakukan kajian kritis terhadap profetologi menurut ʿAbd al-Ḥalim Maḥmud. Ruggero juga menawarkan pendekatan tematik yang komprehensif tentang tema-tema kenabian untuk melawan fundamentalisme dan menyelesaikan konflik di beberapa komunitas Muslim. Pendekatan teologis dalam hadis yang ditawarkan oleh Ruggero mendefinisikan hadis sebagai transmitted testimony. Sementara kajian hadits klasik yang menempatkan hadits sebagai sumber hadis kenabian yang berfokus pada transmisi dan Orientalisme/Studi Islam menempatkan hadits sebagai sejarah dan dokumen yang menggambarkan sosial dan budaya masyarakat Muslim masa lalu, Ruggero ingin mengintegrasikan kedua pendekatan tersebut dan membawanya ke dalam dialog.]